Recent Advances on High‐Entropy Alloys for 3D Printing. Issue 26 (20th May 2020) - Han, Changjun; Fang, Qihong; Shi, Yusheng; Tor, Shu Beng; Chua, Chee Kai; Zhou, Kun
Abstract: Boosted by the success of high‐entropy alloys (HEAs) manufactured by conventional processes in various applications, the development of HEAs for 3D printing has been advancing rapidly in recent years. 3D printing of HEAs gives rise to a great potential for manufacturing geometrically complex HEA products with desirable performances, thereby inspiring their increased appearance in industrial applications. Herein, a comprehensive review of the recent achievements of 3D printing of HEAs is provided, in the aspects of their powder development, printing processes, microstructures, properties, and potential applications. It begins with the introduction of the fundamentals of 3D printing and HEAs, as well as the unique properties of 3D‐printed HEA products. The processes for the development of HEA powders, including atomization and mechanical alloying, and the powder properties, are then presented. Thereafter, typical processes for printing HEA products from powders, namely, directed energy deposition, selective laser melting, and electron beam melting, are discussed with regard to the phases, crystal features, mechanical properties, functionalities, and potential applications of these products (particularly in the aerospace, energy, molding, and tooling industries). Finally, perspectives are outlined to provide guidance for future research. Abstract : 3D printing of high‐entropy alloys (HEAs) has great potential for manufacturing geometrically complex and/or customized HEA products with desirable performances, inspiring their increased appearance in industrial applications. A comprehensive review of the recent advances on the 3D printing of HEAs is provided, with regard to the aspects of their powder development, printing processes, microstructures, mechanical properties, functionalities, and potential applications.